Human Development and the Business Model Impact of Bitcoin Transactions - Saputro, Janu Ilham; Rahmadani, Ade Agung; Sriyono, Diaz Mauludin; Yuliyanto, Hizkia; Silaban, Nia Adelina (Blockchain Frontier Technology, 2023)
This essay provides characteristics of three emerging business models to comprehend the logic and importance of business model design about the impact of bitcoin transactions on human development. This essay argues that a business model is a social construction that describes how value is produced, and that value production requires human agency. The creation of value through a human agency is demonstrated by the use of bitcoins. Some businesses are changing how they conduct business as a result of the decentralization of financial transactions in a global internet information architecture. The highest volume of cryptocurrency exchanged to date, bitcoin, is supported by this infrastructure. It seems that bitcoin is having an impact on new company models. However, little is known about the development of these models and their implications. This paper provides a theoretical framework for understanding the logic and worth of business models about the use of bitcoin and human agency. It examines the impact of bitcoin transactions on human development. The results show that where people have access to the internet, there is a favorable association between bitcoin transactions and human development. Cluster analysis is used to analyze the logic and value of business model design from the bitcoin effect based on various variables. The evolving paradigms that each of these nations represents are divided into three groups. This paper's contribution is to reveal the bitcoin effect, which is evident in the new business models it makes possible. Based on the logic of its design, this can be used as a lens to analyze the value produced by a bitcoin business model.